The Importance of Agribusiness Five Sub-System in The Cocoa Development in West Sulawesi - Harli, Nurlina; Irham, Irham; Jamhari, Jamhari (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2018)
West Sulawesi Province is one of cocoa production centers in Indonesia. This study aims to determine: (1) Level of importance of criteria in cocoa agribusiness development, (2) Level of importance of subcriteria in cocoa agribusiness development, and (3) Choosing appropriate priority strategy in cocoa agribusiness development. Primary data and secondary data was used and analyzed usingÂ Analytical Hierarchy Process (AHP) with Expert Choice 11.0.Â Resulting analysis showed that the most important criterion in the development of cocoa agribusiness in the upstream subsystem, the following priorities respectively are marketing subsystem, cultivation subsystem, supporting subsystem, processing subsystem. The priority criterion in upstream agribusiness subsystem was on the subcriteria availability of cocoa seeds. Increasing cocoa production was the priority criterion in cultivation subsystem. The priority criterion in processing subsystem was subcriteria of capital availability. The Cocoa quality improvement was the priority in the marketing subsystem. The priority criterion in supporting subsystem was subcriteria of infrastructure improvement. The main priority of alternative strategy was to rejuvenate old plants using qualified plant material to increase production and quality of yield weighted as 0.241.